Paulus als Yischmaelit? The Personification of Scripture as Interpretive Authority in Paul and the School of Rabbi Ishmael - Cover, Michael (Journal of Biblical literature, 2016)
While a growing body of scholarship suggests that Paul's scriptural hermeneutics may fruitfully be illuminated "backwards" in the light of his early Christian reception and interpretation, the enigma of the precise Jewish character of his exegetical method remains tantalizingly unsolved. Any attempt to illuminate this obscurity by way of Paul's Jewish matrix must wrestle with one intractable fact and its correlative question: Paul was a Pharisee (Phil 3:5), but what kind of Pharisee? Past answers to this question in terms of various first-century rabbis-- as exemplified by the studies of Joachim Jeremias, Hans Hübner, and, more recently, N. T. Wright--stumble upon the methodological skandalon of the late dating of Tannaitic sources. The present article proposes a new way through this impasse, in the form of a twofold contribution. First, a comparison of the scriptural hermeneutics of the Pauline letters--particularly Galatians--and the midrash attributed to the school of Rabbi Ishmael reveals an important and overlooked similarity: their common personification of "Scripture" as a selfinterpreting authority. Triangulating between this common complex of hermeneutical features and Essene and Alexandrian exegetical methods, one can then recover with reasonable probability some contours of Paul's first-century Pharisaism that have ramifications for understanding Paul's Jewish education, his relationship to Torah, and his apocalypticism and mysticism.